Students’ errors in solving problems involving the polar form of complex numbers: An analysis based on kastolan’s stages - Lubis, Nur Ainun; Zaiyar, M.; Harahap, Rosliana; Umar, Ali (Al-Jabar: Jurnal Pendidikan Matematika, 2026)
Purpose: The application of Kastolan's error analysis framework to the polar form of complex numbers remains limited, leaving a gap in the diagnostic literature for undergraduate mathematics education. This study aims to describe and classify the errors made by students when solving complex number polar form problems based on Kastolan's error stages: conceptual, procedural, and technical, to provide an empirical basis for more targeted instructional strategies in complex analysis.Method: A qualitative descriptive approach was employed. Data were collected through a written descriptive test and documentation of student answer sheets, which were analysed using Kastolan's error classification rubric. The research subjects were 21 seventh-semester Mathematics Education students at UIN North Sumatera who had completed the Complex Analysis course. Three students were selected through purposive sampling to represent each dominant error category.Findings: Three dominant error types were identified. Conceptual errors appeared in incorrect identification of arguments and angular quadrants. Procedural errors occurred when students bypassed the required polar form in division operations. Technical errors involved incorrect values of special angles and trigonometric function signs.Significance: These findings provide an empirical basis for lecturers to design targeted learning strategies addressing concept understanding, procedural order, and computational accuracy in complex number polar form instruction.